Traffic air pollution monitoring based on an air-water pollutants deposition device - Silva, L. T. (2014)
An air water surface sampler device was developed and used to evaluate the atmosphere deposition due to the urban traffic air pollution in the business center of a mid-sized city. The indicator adopted to assess the cumulative air pollutant deposition in the surface of the device was the electric conductivity that was measured on a regular basis during the experiment. Additionally a digital camera was used to count the passing traffic in the road of the study site. Water samples were also taken from the device reservoir and dissolved metals concentrations (Cooper, Iron and Zinc) and acidity/alcalinity were determined in the laboratory. The obtained results were compiled and analyzed in order to evaluate the performance of the device and the relation between the atmospheric deposition and the traffic activity under different meteorological conditions. The research successfully proved that the device was able to evaluate the impact of pollutant emissions related to city traffic. It was also proved that electric conductivity can be used as an indicator to evaluate the cumulative deposition of air pollutants from road traffic. A significant correlation (Spearman rank) between the accumulated traffic and electric conductivity (dry period: ϱ= 0.991626 and wet period: ϱ= 0.810526) was observed.